Alterations in Immune Response Profile of Tumor-Draining Lymph Nodes after High-Intensity Focused Ultrasound Ablation of Breast Cancer Patients - Xue-Qiang Zhu; Pei Lu; Zhong-Lin Xu; Qiang Zhou; Jun Zhang; Zhi-Biao Wang; Feng Wu (Cells, 2021)
Previous studies have revealed that high-intensity focused ultrasound (HIFU) ablation can trigger an antitumor immune response. The aim of this study was to investigate immune response in tumor-draining lymph nodes (TDLNs) after HIFU treatment. Forty-eight female patients with biopsy-confirmed breast cancer were divided into a control group and an HIFU group. In the control group, 25 patients underwent modified radical mastectomy, but 23 patients in the HIFU group received HIFU ablation of primary cancer, followed by the same operation. Using HE and immunohistochemical staining, the immunologic reactivity pattern and immune cell profile were assessed in paraffin-embedded axillary lymph nodes (ALNs) in all patients. The results showed that ALNs presented more evident immune reactions in the HIFU group than in the control group (100% vs. 64%). Among the ALNs, 78.3% had mixed cellular and humoral immune response, whereas 36% in the control group showed cellular immune response. The numbers of CD3+, CD4+, NK cell, and activated CTLs with Fas ligand+, granzyme+ and perforin+ expression were significantly higher in the ALNs in the HIFU group. It was concluded that HIFU could stimulate potent immune response and significantly increase T cell, activated CTLs and NK cell populations in the TDLNs of breast cancer.